2021
DOI: 10.1186/s12913-020-06013-8
|View full text |Cite
|
Sign up to set email alerts
|

Outreach-based clinical pharmacist prescribing input into the healthcare of people experiencing homelessness: a qualitative investigation

Abstract: Background Severely and multiply disadvantaged members of the homeless population are disproportionately vulnerable to exceptionally high levels of multi-morbidity and premature death. Given widespread calls for the development of interventions that might improve the uptake and effectiveness of healthcare for this population, this study investigated patient and other stakeholder perspectives regarding an outreach service, delivered by prescribing pharmacists in collaboration with a local volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…We also learned that models of delivery of HCV care should be collaborative and patient-centered, and that they should also be “low-barrier” with flexible scheduling and multiple opportunities for engagement. These learnings echo the findings of other studies that have explored the perspectives of PWID and people experiencing homelessness related to receiving healthcare [ 41 , 42 ], and reinforce the role of multi-level stigma as a major barrier to HCV care. The acceptability of a community pharmacy model for HCV among these PWID was mixed, and appeared in part influenced by a lack of familiarity with pharmacists’ training and scope of practice.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We also learned that models of delivery of HCV care should be collaborative and patient-centered, and that they should also be “low-barrier” with flexible scheduling and multiple opportunities for engagement. These learnings echo the findings of other studies that have explored the perspectives of PWID and people experiencing homelessness related to receiving healthcare [ 41 , 42 ], and reinforce the role of multi-level stigma as a major barrier to HCV care. The acceptability of a community pharmacy model for HCV among these PWID was mixed, and appeared in part influenced by a lack of familiarity with pharmacists’ training and scope of practice.…”
Section: Discussionsupporting
confidence: 80%
“…Pharmacy models have also been demonstrated to reduce barriers to care for people experiencing homelessness. Johnsen, et al (2021), for example, found that not only was their outreach pharmacist model acceptable for people experiencing homelessness, it reduced barriers and further encouraged engagement in care by “capitalizing on windows of opportunity” that patients had to get treated [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 Qualitative studies show that PEH value such dedicated services. 27 , 28 Establishment of tailored interventions, including outreach-based services, have been advocated in the NHS L ong T erm P lan . 29 There is also scope to widen the roles of community pharmacies as PEH utilise pharmacies on a regular basis for substance misuse treatment, needle exchange, and prescription collection.…”
Section: Discussionmentioning
confidence: 99%
“…Caseloads for the full intervention were experienced as high overall, but the flexibility of the role allowed the PNs to respond nimbly, providing more or less intensive support to individuals at any given time to manage this. This was experienced as following a PIEs approach, as well as fitting with an emerging evidence base which highlights the importance of flexible and person-centred support for those that are severely and multiply disadvantaged [ 94 ]. The PNs were proud of their role and the achievements of participants.…”
Section: Discussionmentioning
confidence: 99%